Contribution of amylose-procyanidin complexes to slower starch digestion of red-colored rice prepared by cooking with adzuki bean - Morina, Filis; Hirota, Sachiko; Takahama, Umeo (International journal of food sciences and nutrition, 2020)
Combining high-carbohydrate food with polyphenol-rich food is a possible way of producing slowly digestible starch with beneficial health properties. In Japan, non-glutinous and glutinous rice are cooked with adzuki bean and the colour of the cooked rice is pale red. In this article, we show that (1) the red colour of rice could be attributed to the oxidation of adzuki bean procyanidins, (2) pancreatin-induced starch digestion of the red-coloured non-glutinous rice was slower than white rice and (3) the digestion of amylose and potato starch but not amylopectin became slower by heating with procyanidin B2. Furthermore, the rate of starch digestion of red-coloured rice was not affected by nitrite treatment under simulated gastric conditions. The above results show that procyanidins could bind to amylose independent of the starch source by heating and could suppress starch digestion by α-amylase in the intestine.
Keywords: Cooking; amylopektin; Humans; rýže (rod); vysoká teplota; Pancreatin; Hot Temperature; amylopectin; Japonsko; Digestion; glutinous and non-glutinous rice; Amylose; Proanthocyanidins; Adzuki bean; lidé; Japan; Catechin; vaření; amylose; Vigna; Oryza; trávení; alpha-Amylases; procyanidins; alfa-amylasy; amylosa; Amylopectin; vigna; Biflavonoids; biflavonoidy; pankreatin; katechin; proantokyanidiny